Analysis of The Effect of INA CBGs Diagnoses on Costs in Outpatient THT Specialist Poly Hospital X Surabaya - Roesbiantoro, Andi; Aan Adriansyah, Agus; Dany Afina, Rizka; Sa'adah, Nikmatus; Setianto, Budhi (Universitas Nahdlatul Ulama Surabaya, 2025)
BPJS Kesehatan will pay to advanced referral Health Facilities. BPJS Kesehatan pays with the INA CBG's (Indonesia Case Base Groups) package system. INA CBGs is a payment system with a package system based on the diseases suffered by patients (1) knowing the disease pattern in the ENT-KL Polyclinic of RSX Surabaya, (2) calculating the unit cost of the 10 most common diseases, (3) calculating the relationship between age range and INA CBGs coding on drug costs using the relationship test. The method used in this research is a retrospective descriptive study. The population and sample of this study were BPJS patient data. The type of data used was TXT secondary data in the outpatient ENT clinic. The type of data used is secondary data from BPJS patient, the total sample was a population of 750. The data was processed using Chi-Square. From this study, it was found that most of the BPJS patients of the ENT Poli of X Hospital were male, with the highest age range being at the age of 51 - 55 years, with the INA CBGs coding being Q - 5 - 44 - 0 with the diagnosis of Tinnitus / Ringing in the ears with the total average difference per patient against hospital tariff financing compared to the INA CBGs Tariff was 83,593. There is a relationship between the Age Range and INA Cbgs coding on the funding in the Pharmacy Unit, which is ENT.